2020
DOI: 10.19128/turje.658198
|View full text |Cite
|
Sign up to set email alerts
|

Does soft skill development vary among the students? A gender perspective

Abstract: The study was intended to examine the extent to which soft skill development varied among the university students by gender via their participation in co-curricular activities (CCAs). Moreover, the study aimed to find out whether there was a significant difference between male and female students concerning soft skill development. The study has shown that males have developed diverse personal skills and social skills, that is, soft skills more than females excepting one which is presentation skill. The study h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…The concept of an individual with social responsibility is someone aware of his selfesteem and responsible for his thoughts, feelings and behaviour that can meet his needs. It will bear the consequences when it does not carry out (Gokalp & Inel, 2021;Siddiky, 2020). The characteristics of the attitude of responsibility include being able to carry out tasks on time, having self-control and discipline under any circumstances, having accountability, being ready to be held accountable and ready to be held accountable, having consideration or consequences of the actions experienced, and always showing perseverance, diligence.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of an individual with social responsibility is someone aware of his selfesteem and responsible for his thoughts, feelings and behaviour that can meet his needs. It will bear the consequences when it does not carry out (Gokalp & Inel, 2021;Siddiky, 2020). The characteristics of the attitude of responsibility include being able to carry out tasks on time, having self-control and discipline under any circumstances, having accountability, being ready to be held accountable and ready to be held accountable, having consideration or consequences of the actions experienced, and always showing perseverance, diligence.…”
Section: Introductionmentioning
confidence: 99%
“…Bangladesh scientist M. R. Siddiky (2020) found that gender makes a significant impact on the soft skills development, except for the development of presentation skills. Therefore, he points to the necessity for a more detailed study of cultural and social factors that influence the development of students' soft skills based on their gender (Siddiky, 2020).…”
Section: Introductionmentioning
confidence: 99%